(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to examine the influence of total quality management on competitive advantage in some banks operating in Erbil, Iraq. The research starts from a conceptual outline that takes into account the nature of the relationship between total quality management and competitive advantage. Accordingly, the research hypotheses were developed, and in order to fulfill the research requirements, the researcher prepared a theoretical framework and made good use of the subject literature, then chose the number of banks in Erbil city to perform and obtain empirical data. The research sample included 53 bank managers. A questionnaire was also established to collect data. To analyze data, we used some statistical methods, and the hypotheses were tested. The results indicated that leadership, management of staff, information and analysis, and customer attention have been found to be strong predictors of banks competitive advantage in Erbil, Iraq.